Ways of innovative academic delusional transformations - Dimitar Blagoev (Zenodo, 2022)
After dynamic weather through autumn season, Europe has seen a lot of changes back and forth also this month. It’s actually been quite wintery in many areas, we could say the start of the first winter month is good. Now, with a powerful Omega blocking High established across western Europe and North Atlantic, a massive cold outbreak blast into parts of Europe this week. But with such a progressive weather pattern, what are the odds for white Christmas forecast across Europe this year? Let’s see the final weather model trends.